The System of Government Commissioners during the First World War and the organization of the Government High Commissioner’s Office in Transylvania - JUDIT, Pál (Studia Universitatis Babeș-Bolyai Historia, 2018)
The study presents the establishment and usage of the system of state commissioners during the First World War. Related to this topic it also presents the establishment of the institution of the regional commissioner’s office for Transylvania and of the Government High Commissioner’s Office for Eastern Hungary created in December 1918. The appointment of state commissioners and the organization of state commissioner’s offices impaired local governments, and the research analyses how this process unfolded and how the transition to the circumstances that developed after the war took place. Rezumat: Sistemul comisarilor guvernamentali în timpul Primului Război Mondial şi organizarea Înaltului Comisariat Guvernamental în Transilvania. Studiul prezintă înfiinţarea şi utilizarea sistemului comisarilor statului în timpul Primului Război Mondial, inclusiv înfiinţarea instituţiei comisariatului regional pentru Transilvania şi a Înaltului Comisariat Guvernamental pentru Ungaria de Est în decembrie 1918. Numirea comisarilor statului şi organizarea acestei instituţii a afectat sistemul administraţiei locale, iar cercetarea analizează evoluţia procesului şi modul în care s-a desfăşurat tranziţia înspre situaţia de după război. Cuvinte-cheie: comisari guvernamentali, Primul Război Mondial, Transilvania, Înaltul Comisariat Guvernamental pentru Ungaria de Est, autorităţi paralele, situaţie excepţională.